An Overview of Anxiety Prevention with Decreased Anxiety Levels in the Preoperative Room: A Cross-Sectional Study - Setyaningsih, Rahayu; Waluyo, Sunaryo Joko (Universitas Muhammadiyah Surakarta, 2025)
Anxiety can occur in patients who are about to undergo surgery in the operating room. This can disturb the patient's hemodynamics including increased blood pressure, increased pulse and increased respiration. If there are no anxiety prevention measures then surgery may be delayed due to the effects of anxiety. This study described the prevention of anxiety carried out by anesthesiologists in the preoperative room in order to maintain patient hemodynamics so that surgery can be performed according to schedule and procedure. The purpose of this study was to determine the description of anxiety prevention with a decrease in anxiety levels in patients in the preoperative room. The research method descriptive-analytic research method with a cross-sectional research design, the samples were patients who performed surgery in the preoperative room of several hospitals that had been selected, sampling technique with purposive sampling during October-December 2024, data collection methods with questionnaires, instruments using questions that are included in the google form to be filled in by anesthesiologists, data collection methods with google form through WA groups, data analyzed with univariate analysis. The results showed that the actions taken to prevent the most were to create a therapeutic atmosphere to foster trust by providing explanations to patients and families, providing a comfortable environment, minimizing pain, creating a therapeutic relationship between health workers and the patient. The conclusion of the several actions taken by anesthesia stylists to reduce patient anxiety levels, the most chosen is the action of creating a therapeutic atmosphere to create trust between health workers and patients so it is recommended that this action be carried out also by other health workers to help patients in the preoperative room